Routledge handbook of ethics and war just war theory in the 21st century - Allhoff, Fritz; Evans, Nicholas G. 1985-; Henschke, Adam 1976- (Routledge handbooks, 2013)
Offers a comprehensive overview of contemporary extensions and alternatives to the just war tradition in the field of the ethics of war